1997
DOI: 10.1073/pnas.94.21.11168
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage during aging targets mitochondrial aconitase

Abstract: The mechanisms that cause aging are not well understood. The oxidative stress hypothesis proposes that the changes associated with aging are a consequence of random oxidative damage to biomolecules. We hypothesized that oxidation of specific proteins is critical in controlling the rate of the aging process. Utilizing an immunochemical probe for oxidatively modified proteins, we show that mitochondrial aconitase, an enzyme in the citric acid cycle, is a specific target during aging of the housefly. The oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
359
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 581 publications
(379 citation statements)
references
References 49 publications
17
359
0
3
Order By: Relevance
“…7 of this study), by metal-catalyzed oxidation (Gutierrez-Correa and Stoppani, 1995), as well as by the myeloperoxidase system (Gutierrez-Correa and Stoppani, 1999). Our observation that DLDH did not lose activity and did not become more susceptible to oxidative inactivation during aging not only indicate that DLDH is stable during brain aging, but also confirm the notion that protein oxidation during aging is a highly selective process (Das, et al, 2001, Jana, et al, 2002, Toroser, et al, 2007, Yan, et al, 1997, Yan, et al, 2000. Additionally, given that mitochondrial ROS generation capacity does not change during postnatal brain development (Schonfeld and Reiser, 2007), it is reasonable to think that the lower DLDH dehydrogenase activity observed in rat pups is not a consequence of oxidative stress, but rather an adaptive component of postnatal development reflective of changes in energy demand.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…7 of this study), by metal-catalyzed oxidation (Gutierrez-Correa and Stoppani, 1995), as well as by the myeloperoxidase system (Gutierrez-Correa and Stoppani, 1999). Our observation that DLDH did not lose activity and did not become more susceptible to oxidative inactivation during aging not only indicate that DLDH is stable during brain aging, but also confirm the notion that protein oxidation during aging is a highly selective process (Das, et al, 2001, Jana, et al, 2002, Toroser, et al, 2007, Yan, et al, 1997, Yan, et al, 2000. Additionally, given that mitochondrial ROS generation capacity does not change during postnatal brain development (Schonfeld and Reiser, 2007), it is reasonable to think that the lower DLDH dehydrogenase activity observed in rat pups is not a consequence of oxidative stress, but rather an adaptive component of postnatal development reflective of changes in energy demand.…”
Section: Discussionsupporting
confidence: 78%
“…For example, mitochondrial aconitase (Yan, et al, 1997, Yarian, et al, 2006 and adenine nucleotide translocase can lose their functional activities due to age-related oxidative damage. Interestingly, DLDH, as a redox enzyme, does not incur age-related oxidative inactivation in the rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has demonstrated, by two different methods, that histone H1 is one of the nuclear proteins modified by carbonyl groups in i o. The immunological method for the detection of oxidized proteins, based on the derivatization of protein-bound carbonyl groups with DNPH and subsequent detection of the DNP-epitopes by immunoblotting [32], has led to the identification of a number of proteins that accumulate oxidative damage during the aging process [33]. The successful application of this method to detect histone carbonyl groups should facilitate the study of histone carbonylation under different physiological conditions.…”
Section: Discussionmentioning
confidence: 78%
“…High peroxidation rates would be accompanied by elevated ROS levels in the cell. We assayed aconitase activity as a very sensitive and early sensor of ROS levels in the cell, since its activity is quickly lost by oxidation-mediated loss of Fe from its Fe-S prosthetic group (Yan et al, 1997).…”
Section: Apod Deficiency Increases Lipid Peroxides In Astrocytes Withmentioning
confidence: 99%